A new index for assessing heavy metal contamination in sediments of the Beijing-Hangzhou Grand Canal (Zaozhuang Segment): A case study. (October 2016) - Zhuang, Wen; Liu, Yongxia; Chen, Qing; Wang, Qian; Zhou, Fengxia
Abstract: Zaozhuang Segment of the Beijing-Hangzhou Grand Canal is an important water conveyance line on the eastern route of the South-North Water Transfer Project in China and its water environment condition can exert a significant influence on diversion water quality safety. This paper analyzed contents of five heavy metals such as Cd, Cu, Ni, Pb and Zn as well as their chemical forms in surface sediments in this region. Methods including Threshold Effects Level-Probable Effects Level (TEL-PEL), Risk Assessment Code (RAC) and Acid Volatile Sulfide- Simultaneously Extracted Metals (AVS-SEM) were also employed to evaluate the quality of sedimentary environment in this region. With the aim to assess the eco-environmental risk revealing the information of the concentration, the chemical fractionation, the toxicity of heavy metals, a new assessment index known as Multivariable Evaluation Index (MEI) was introduced into this paper. Results indicated that contents of such five heavy metals in surface sediments were generally low. Overall, ecological risk was in the medium-low grade in addition to several locations where the level of risk was high. However, certain differences still existed among various assessment results. Comparing with other single evaluation methods, MEI may be able to reflect contamination status and ecological risks of heavy metals in sediments of a specific region more comprehensively. MEI also seemed able to overcome the limitations of other prevalent aggregated indexes to assess potential sediment pollution risk in aquatic systems.